2020
DOI: 10.3390/ijms21228562
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Stress/Immunological Markers in Crohn’s Disease and Ulcerative Colitis

Abstract: There is continuous and growing interest in research into new alternatives to standard biomarkers to detect and follow-up disease, reducing physical and psychological stress in patients needing regular and invasive medical examinations for the evaluation of pathologies, including inflammatory bowel diseases (IBD). Saliva is one of the most promising body fluids in the research of new biomarkers, thanks to the large number of molecules it contains. Many molecules present in saliva are often directly correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…Finamore et al demonstrated a link between saliva and intestinal profiles in patients with inflammatory bowel diseases (IBD), and this result suggests that, even in athletes, saliva sampling can also be used as a biomarker for gut disease in the oral–gut axis [ 23 ].…”
Section: The Oral Ecosystem and The Saliva Diagnostic Functionmentioning
confidence: 99%
“…Finamore et al demonstrated a link between saliva and intestinal profiles in patients with inflammatory bowel diseases (IBD), and this result suggests that, even in athletes, saliva sampling can also be used as a biomarker for gut disease in the oral–gut axis [ 23 ].…”
Section: The Oral Ecosystem and The Saliva Diagnostic Functionmentioning
confidence: 99%
“…In recent years, the changes in expression levels and expression patterns of salivary proteins under different disease states and physiological conditions have made them an essential breakthrough in studying the etiology, diagnosis and prognosis of these diseases (Zian et al, 2018;Finamore et al, 2020;Tvarijonaviciute et al, 2020). Changes in salivary protein in states of different blood glucose levels have become a hot spot in the study of the relationship between the oral cavity and diabetes (Bencharit et al, 2013;Lima-Aragão et al, 2016).…”
Section: Analysis Of the Discriminating Ability Of Candidate Proteinsmentioning
confidence: 99%
“…Lipid peroxidation, the oxidative damage of membrane lipids, unless disrupted by antioxidants at initiation, spreads quickly in a self-perpetuating, unstoppable chain reaction that intensifies the oxidative destruction [ 5 , 6 ]. The marker of this process is Thiobarbituric Acid Reactive Substances (TBARS) level [ 12 ]. Estimation of TBARS reflects the malondialdehyde (MDA) concentration- the final product of lipid peroxidation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%